Structural changes in ports and the competitiveness of Latin American and Caribbean foreign trade (UN.ECLAC SangiagoCL, 1990)
Evaluates the transformations occurring in port services, markets, technologies and their legal environment, and their utilization in order to identify the directions in which the industry is moving. Makes suggestions for port policies and plans that Latin America and Caribbean might consider.
DC